Effect of phosphorus fertilization and molybdenum seed treatment on yield and economics of soybean: EFFECT OF PHOSPHORUS AND MOLYBDENUM SEED TREATMENT ON SOYBEAN - T SPANDANA; K BHANU REKHA; S N SUDHAKARA BABU (Journal of Oilseeds Research, 2021)
A field experiment was carried out on Alfisols during rainy season 2015 at CollegeFarm, College ofAgriculture, PJTSAU, Rajendranagar, Hyderabad, Telangana to find the effect of soil application of phosphorus fertilizer and molybdenum seed treatment on soybean. Results revealed that soil application of 60 kg P2O5 recorded significantly higher yield attributes (seeds/pod), N uptake by seed (117.0 kg/ha), protein content (41.0 %), seed yield (1784 kg/ha) besides higher gross (` 59,220/ha), net returns (` 39,520/ha) and B:C ratio (3.0). Similarly seed treatment with molybdenum@ 6 g/kg registered higher yield attributes (seeds/pod), N uptake by seed (101.6 kg/ha), protein content (40.2 %), seed yield (1572 kg/ha) apart from gross, net returns and B:C ratio (` 49,872/ha, ` 31,892/ha and 2.78) respectively.